Legal Challenges and Developments in the WTO Dispute Resolution Mechanism - Bagdat Amandossuly; Karlygash Baizhomartova; Zhanat Zhailau; Lyazzat Nyssanbekova; Aidana Otynshiyeva (UIN Sunan Gunung Djati, 2025)
The WTO dispute settlement mechanism plays a critical role in maintaining the stability and fairness of international trade law, offering member states a structured process for resolving trade conflicts. Its relevance is underscored by its capacity to enforce multilateral agreements and ensure compliance with trade obligations, thereby protecting the interests of both developed and developing nations. However, significant challenges, such as procedural delays and the lack of interim economic protections for claimants, reveal the mechanism's limitations, especially for economically weaker states. This study focuses on the legal aspects of the WTO dispute settlement system, particularly its effectiveness in addressing disputes and safeguarding the rights of member states. The research emphasizes the weaknesses in compensation mechanisms and procedural fairness, while also evaluating the role of the Appellate Body and its recent paralysis as critical challenges to the system's functionality. The study employs a qualitative analysis of WTO agreements, case studies, and statistical data to examine the practical implications of the dispute settlement mechanism's limitations. By evaluating specific cases such as DS530 (Ukraine v. Kazakhstan) and DS611 (EU v. China), the research highlights the legal complexities and procedural shortcomings that affect equitable dispute resolution. The findings reveal the urgent need for reforms, including the introduction of interim relief measures, improved compensation mechanisms, and enhanced representation for developing countries. Recommendations also address the optimization of Appellate Body functionality and adapting the WTO legal framework to emerging trade challenges, such as digital commerce and sustainability. These reforms are essential for ensuring the continued relevance and equity of the WTO dispute settlement mechanism in a rapidly evolving global trade environment.